"One‐for‐All" Strategy in Fast Energy Storage: Production of Pillared MOF Nanorod‐Templated Positive/Negative Electrodes for the Application of High‐Performance Hybrid Supercapacitor. Issue 23 (2nd May 2018) - Qu, Chong; Liang, Zibin; Jiao, Yang; Zhao, Bote; Zhu, Bingjun; Dang, Dai; Dai, Shuge; Chen, Yu; Zou, Ruqiang; Liu, Meilin
Abstract: Currently, metal‐organic frameworks (MOFs) are intensively studied as active materials for electrochemical energy storage applications due to their tunable structure and exceptional porosities. Among them, water stable pillared MOFs with dual ligands have been reported to exhibit high supercapacitor (SC) performance. Herein, the "One‐for‐All" strategy is applied to synthesize both positive and negative electrodes of a hybrid SC (HSC) from a single pillared MOF. Specifically, Ni‐DMOF‐TM ([Ni(TMBDC)(DABCO)0.5 ], TMBDC: 2, 3, 5, 6‐tetramethyl‐1, 4‐benzenedicarboxylic acid, DABCO: 1, 4‐diazabicyclo[2.2.2]‐octane) nanorods are directly grown on carbon fiber paper (CFP) (denoted as CFP@TM‐nanorods) with the help of triethylamine and function as the positive electrode of HSC under alkaline electrolyte. Meanwhile, calcinated N‐doped hierarchical porous carbon nanorods (CFP@TM‐NPCs) are produced and utilized as the negative counter‐electrode from a one‐step heat treatment of CFP@TM‐nanorods. After assembling these two electrodes together to make a hybrid device, the TM‐nanorods//TM‐NPCs exhibit a wide voltage window of 1.5 V with a high sloping discharge plateau between 1‐1.2 V, indicating its great potential for practical applications. This as‐described "One‐for‐All" strategy is widely applicable and highly reproducible in producing MOF‐based electrode materials for HSC applications, which shortens the gap between experimental synthesis and practical application of MOFs in fast energy storage. Abstract : A "One‐for‐All" design strategy is applied to fabricate both hybrid supercapacitor positive/negative electrodes from a single pillared metal–organic framework. The as‐fabricated device exhibits high energy density at elevated power of 17 104 W kg −1, and the capacitance retention is 83.2% after 10 000 cycles at 10 A g −1, demonstrating the viability and potential of this hybrid device for practical applications.